Investigating "circular business models" in the manufacturing and service sectors. Issue 3 (15th April 2019) - Upadhyay, Arvind; Akter, Shaheda; Adams, Lindsay; Kumar, Vikas; Varma, Nikhil
Abstract : Purpose: The purpose of this paper is to investigate the role of the different circular business models (CBMs) in the manufacturing and service sector and apply this in the context of the food industry (FI), through a systematic literature review of related published journals and articles. The research study is designed to illustrate the impact of CBMs in the manufacturing and service sectors through a combination of real-life examples and direct references to existing literature. Design/methodology/approach: The underlying research study follows a systematic literature review approach where the relevant CBMs are explored in the context of the manufacturing and service sector (FI.) The journals most cited in the context of CBMs and their implication in the manufacturing and service sector were chosen for this study. There was no fixed timeframe applied to complete the research. A total of 54 articles were selected which referenced: discussion in the context of the concept of CBMs; different types of CBM; definition of the manufacturing sector; definition of the service sector (FI); application of different CBMs in these two sectors; and included a comparison of the application of CBMs. In total, 40 of the 54 articles were shortlisted for best relevance and used in the research study. Findings: The underlying research study was limited to 40 articles and the data contained within them. The article search was limited to the keywords of the CBM; the implication of CBM; the CBM in manufacturing (textiles); circular business in service (FI); and comparison and application of the CBM. Practical implications: The final analysis demonstrates that circular business promotes sustainability by allowing companies to generate maximum return from given resources and reach zero waste targets. Greater customer satisfaction is also achieved through service innovation that cuts down negative impact on the environment. These findings are relevant and applicable to the FI. Originality/value: A review of existing literature showed that whilst there is significant research on the implications of the CBM in general, there has been little focus on the use of different CBMs specifically in the manufacturing and service industry (FI). This research study is designed to tease out the specific benefits of CBMs in this context, highlighting the contribution they can make to efficiency in both the manufacturing and service sectors (FI) through useful comparison.